IMPLEMENTASI EVENT PROCEDURE PADA ACCESS 2007 UNTUK MEMBUAT APLIKASI KALKULATOR - Suharnawi Suharnawi Suharnawi (Semantik, 2011)
Calculator is a calculating tool that is still used by many people. Calculator have many advantages, including the ease of use to perform calculations. Its relatively small size makes it easy to carry and in addition it also has a low price. Once the importance of calculators in the activity of the everyday, a lot of modern equipment which also contains embedded calculator application. Handphone also has the ability to perform calculations with a calculator, a variety of new computer also have the calculator facility. Microsoft Office Access that has the ability to create a Form, can be used to design Calculator Application. To make this calculator application requires the Visual Basic programming language that has been integrated with Microsoft Office Access. The code generation program by utilizing the Event Procedure.Keywords : calculator, computer, Access, Event Procedure